The study of zirconium and hafnium complexes with pyrazolon derivatives and their use in analysis - Shtokalo, Miroslava; Kostenko, Elizaveta; Ostrovska, Mira; Rizhenko, Victoria (My University, 1982)
The optimum conditions of the reaction and the composition of complexes that is formed were found. The complexformation constants were calculated. The Offered scheme of the interaction in systems. Offered methodses of the determination metals.
Keywords: complexformation; definition the metal; фотометрія; комплексоутворення; визначення металів; photometry; кафедра харчової хімії